Reviewing the Impact of Impaired Masticatory Function on the Nutrition and General Health of Completely Edentulous Patients - Suryakant C. Deogade; Dinesh Naitam; Sushant M. Patil (Achievements and Challenges of Medicine and Medical Science Vol. 9, 2024)
Loss of the tooth following its removal from the mouth leads to a frequent condition of deficient masticatory function (MF). Diminished MF can result in functional deficiencies of the tongue, the oral mucosa, the muscles of mastication, the salivary glands, and the nervous system. Individuals suffering from impaired masticatory function may adapt food consistency to their existing dental status or rely on the digestive system to compensate for the lack of oral preparation of food. These circumstances further lead to deficient nutrient intake or increase the likelihood of digestive diseases and decrease gut absorption. Dysfunction of masticatory efficiency thus may be detrimental to general health. This article reviews different methods of evaluating MF objectively and subjectively. It also enlightens the evidence of the effects of masticatory deficiency on nutrition and mentions the various issues related to study design, confounding variables, and the subjective nature of the measurements in the reviewed literature. The reviewed evidence supporting an association between MF and deficient dietary intake often is based on relatively weak correlations and cannot confer a causal relationship between the reviewed variables. A significant correlation between poor oral health and some gastrointestinal diseases has also been established. Public health services must be given stress on the need to preserve natural teeth to enable adequate nutritional consumption, and dental practitioners should be aware of various nutritional risks associated with denture wearing.